If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 4) = 2 + -20 + x Reorder the terms: 3(4 + 2x) = 2 + -20 + x (4 * 3 + 2x * 3) = 2 + -20 + x (12 + 6x) = 2 + -20 + x Combine like terms: 2 + -20 = -18 12 + 6x = -18 + x Solving 12 + 6x = -18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + 6x + -1x = -18 + x + -1x Combine like terms: 6x + -1x = 5x 12 + 5x = -18 + x + -1x Combine like terms: x + -1x = 0 12 + 5x = -18 + 0 12 + 5x = -18 Add '-12' to each side of the equation. 12 + -12 + 5x = -18 + -12 Combine like terms: 12 + -12 = 0 0 + 5x = -18 + -12 5x = -18 + -12 Combine like terms: -18 + -12 = -30 5x = -30 Divide each side by '5'. x = -6 Simplifying x = -6
| -4c+3c=4(c+2) | | m+32=56 | | 2x+1=5x+20 | | 2/3(x-9)=9 | | S=R-0.07R | | 4(3q-7)=4 | | .06(1000-x)+0.10x=80 | | 12q-28=4 | | (2x+9)(4x+12)=0 | | 161=73-v | | 3x-4=4x+5 | | -2x+4=2x+8 | | -2(2y)= | | 5x+24=5(x+5) | | =x^4-9x^2 | | 3d^2-4d=4 | | 5(4y)= | | 3(x-1)=2x-5 | | 11(x+10)=4x+2x+10 | | (t+-5)+2= | | 2x-10=4x+4 | | 3-2(5-x)=3 | | -4+(-5+k)= | | 60x+60= | | X^2+21x-76=0 | | (n+-8)+-2= | | 2x-13=y+4 | | 7w-6w+3= | | 28=0.25x+3 | | 1/2([x]-4)^2=8 | | 41-4x=9-8x | | 6(2-2x)=54 |